Glucocorticoids Promote Extracellular Matrix Component Remodeling by Activating YAP in Human Retinal Capillary Endothelial Cells - Gu, Xianliang; Ge, Lingling; Ren, Bangqi; Fang, Yajie; Li, Yijian; Wang, Yi; Xu, Haiwei (Frontiers in Cell and Developmental Biology, 2021)
Remodeling of extracellular matrix (ECM) components of endothelial cells is the main cause of retinal vascular basement membrane (BM) thickening, which leads to the initiation and perpetuation of microvasculopathy of diabetic retinopathy (DR). Excessive amounts of glucocorticoids (GCs) are related to the presence and severity of DR, however transcriptional effects of GCs on the biology of human retinal capillary endothelial cells (HRCECs) and its impacts on DR are still unclear. Here, we showed that GC (hydrocortisone) treatment induced ECM component [fibronectin (FN) and type IV collagen (Col IV)] expression and morphological changes in HRCECs via the glucocorticoid receptor (GR), which depended on the nuclear translocation of YAP coactivator. Mechanistically, GCs induced stress fiber formation in HRCECs, while blocking stress fiber formation inhibited GC-induced YAP nuclear translocation. Overexpression of FN, but not Col IV, could activate YAP through the promotion of stress fiber formation via ECM-integrin signaling. Thus, a feedforward loop is established to sustain YAP activity. Using mRNA sequencing of HRCECs with overexpressed YAP or GC treatment, we found a similarity in Gene Ontology (GO) terms, differentially expressed genes (DEGs) and transcription factors (TFs) between the two RNA-seq datasets. In vivo, YAP was activated in retina vascular ECs of STZ-induced diabetic mice, and TF prediction analysis of published RNA-seq data of dermal vascular ECs from T2DM patients showed that GR and TEAD (the main transcription factor of YAP) were enriched. Together, GCs activated YAP and promoted ECM component (FN and Col IV) remodeling of retinal capillary endothelial cells, and the underlying regulatory mechanism may provide new insights into the vascular BM thickening of the retina in the early pathogenesis of DR.